2017
DOI: 10.7554/elife.29338
|View full text |Cite
|
Sign up to set email alerts
|

Atg9 antagonizes TOR signaling to regulate intestinal cell growth and epithelial homeostasis in Drosophila

Abstract: Autophagy is essential for maintaining cellular homeostasis and survival under various stress conditions. Autophagy-related gene 9 (Atg9) encodes a multipass transmembrane protein thought to act as a membrane carrier for forming autophagosomes. However, the molecular regulation and physiological importance of Atg9 in animal development remain largely unclear. Here, we generated Atg9 null mutant flies and found that loss of Atg9 led to shortened lifespan, locomotor defects, and increased susceptibility to stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 78 publications
(103 reference statements)
4
47
0
3
Order By: Relevance
“…To verify that the categories of ATG gene results were not simply due to variability with hypomorphic RNAi conditions, we examined null mutants for Atg5, Atg9 , and Stx17 (Kim et al, 2016; Wen et al, 2017; Takáts et al, 2013). Consistent with the RNAi results, loss of Atg9 or Stx17 functions fully blocked tAL formation, while Atg5 null mutants only partially reduced the extent of the tubulated network (Figure 3C–H and Figure 3—figure supplement 1C–E).…”
Section: Resultsmentioning
confidence: 99%
“…To verify that the categories of ATG gene results were not simply due to variability with hypomorphic RNAi conditions, we examined null mutants for Atg5, Atg9 , and Stx17 (Kim et al, 2016; Wen et al, 2017; Takáts et al, 2013). Consistent with the RNAi results, loss of Atg9 or Stx17 functions fully blocked tAL formation, while Atg5 null mutants only partially reduced the extent of the tubulated network (Figure 3C–H and Figure 3—figure supplement 1C–E).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the induction of autophagy can block stress-induced ISC proliferation (47). In addition, Atg9 is also required for midgut homeostasis under normal physiological condition, and it specifically acts in enterocytes to control cell growth by limiting TOR signaling (48). Analysis of various Atg genes in the Drosophila midgut has demonstrated that the Atg1 complex components, including Atg1, Atg13, and Atg17, play crucial roles in controlling enterocytes cell growth (48).…”
Section: Atg101 Regulates Both Neuron and Midgut Homeostasismentioning
confidence: 99%
“…In addition, Atg9 is also required for midgut homeostasis under normal physiological condition, and it specifically acts in enterocytes to control cell growth by limiting TOR signaling (48). Analysis of various Atg genes in the Drosophila midgut has demonstrated that the Atg1 complex components, including Atg1, Atg13, and Atg17, play crucial roles in controlling enterocytes cell growth (48). Furthermore, it appears that the Atg1 complex and Atg9 regulate TOR signaling via different mechanisms during enterocyte cell growth (48).…”
Section: Atg101 Regulates Both Neuron and Midgut Homeostasismentioning
confidence: 99%
See 2 more Smart Citations